Development and application of an automated impulse hammer for improved analysis of five-axis CNC machine dynamics and enhanced stability chart prediction. (30th October 2019) - Postel, Martin; Candia, Nicolas; Bugdayci, Bircan; Kuster, Fredy; Wegener, Konrad
Imprecise frequency response measurements can be a major problem in the analysis of CNC milling machine dynamics. Errors due to limited human capabilities hamper the precision of conventional impact tests using an impact hammer. Furthermore, impact tests on milling machines can be very time-consuming if dedicated parameter studies are performed, and also hazardous if impacts need to be performed on a rotating structure. To overcome these problems, a modularised and automated impulse hammer is presented in this paper. When using the automated impulse hammer, the variance in amplitude of subsequent impulses reveals to be one order of magnitude lower than when excitation is performed by hand. It is illustrated how the automated device can be used to investigate very distinct dynamic effects on a CNC machine that require a very high measurement precision, and also in which cases it helps to obtain more accurate stability chart predictions.